First Balkan Brief Illness Perception Questionnaire (IPQ-B) among high-risk pregnancies - Maja Macura; Jovana Todorović; Vedrana Pavlović; Katarina Ivanović; Ivana Novaković; Miloš Milinčić; Miroslava Gojnić (PLoS ONE, 2025)
Background Pregnancy is a particularly delicate period in which many health-related changes lead to changes in the perception of women’s well-being, in both physiological and especially high-risk pregnancies. In high-risk pregnancies, the relationship between illness perception and general well-being is even more complicated as sometimes there might not be any apparent signs or symptoms, but the pregnant woman or foetus still might be at risk. Aims To assess the validity and reliability of the existing Serbian version of the Brief Illness Perception Questionnaire (B-IPQ) in a specific population of pregnant women with high-risk pregnancies (HRP). Methods This was a cross-sectional study including 290 patients hospitalized at the Clinic for Gynaecology and Obstetrics, University Clinical Centre of Serbia. The research instrument was a questionnaire with six sections: 1) socio-demographic; 2) pregnancy-related; 3) COVID-19 pandemic–related data 4) B-IPQ; 5) The World Health Organization Quality of Life Brief Version (WHOQOL-BREF) and 6) The Depression, Anxiety and Stress Scale – 21 Items (DASS-21). Psychometric properties of the Serbian version of B-IPQ were analysed through factorial structure and internal consistency (reliability). Confirmatory factor analysis (CFA) was performed to confirm the original two-dimensional structure of the IP. Results Analysis of internal consistency of the Serbian version of the eight-item IPQ-B showed that Cronbach’s alpha of the entire scale was 0.7, indicating good scale reliability. IP correlated significantly with QoL related to mental health, stress, anxiety, and depression levels. The consequence domain of IP affected mental health mostly. IP was one of the main direct predictors of QoL and an indirect predictor through depression, anxiety, and stress levels. Marital status, hypertension in pregnancy, fear for health during the COVID-19 pandemic, and being informed during the COVID-19 pandemic had direct negative effects on IP, and indirectly on QoL. Conclusions The Serbian version of IPQ-B has good reliability and validity for illness perception in high-risk pregnancies.